Assessing Patient Compliance and Long-Term Outcomes of Oral Appliances in Sleep Apnea Management - Larry Angel Delgado Martín; Harlee C. Cruzatt; Eloá Vieira Resende (American Journal of Medical Science and Innovation, 2026)
Obstructive Sleep Apnea (OSA) was identified as a common chronic sleep disorder causing serious physiological, psychological, and functional impairments; and Oral Appliance Therapy had been developed as an effective alternative to traditional treatment due to its portability, comfort, and patient satisfaction. The objective of this study was to determine the patient compliance and long-term results (both subjective and objective) of oral appliance therapy in the management of sleep apnea by assessing comfort, ease of use, treatment effects, side effects, patient satisfaction, and their association with long term adherence. A quantitative cross-sectional research design was adopted and data were collected with a structured questionnaire from 422 diagnosed patients of sleep apnea. Sample size was calculated using Cochran’s formula and Analysis & interpretation of the collected data were done by descriptive and inferential statistics using IBM SPSS Statistics. The findings demonstrated high levels of patient adherence, comfort, perceived treatment effectiveness and long-term health improvement among the individuals surveyed. It was also discovered that patient satisfaction levels were high and had a robust acceptance, coupled with an equally strong positive behavioral intention toward continued use of Oral Appliance Usage. Moderate side effects (gastrointestinal or related to the infusion), and difficulties in adjusting behavior confronted by both patients and staff were reported but had no significant impact on continuing treatment. Results indicated that stronger compliance and perceived effectiveness predicted better long-term health states and quality of life outcomes whilst manageable side effects did not influence sustained use. Oral appliance therapy is a successful and patient-centered treatment option for sleep apnea that has proven to make an important contribution to improved clinical outcomes and long-term compliance when administered under proper direction and continuing follow-up care.